2017
DOI: 10.1177/0957154x17698102
|View full text |Cite
|
Sign up to set email alerts
|

‘Details on the Establishment of Doctor Willis, for the Cure of Lunatics’ (1796)

Abstract: The 'mad-doctor' Dr Francis Willis achieved national and international celebrity following his successful treatment of King George III's first major episode of insanity in 1788-9. At the time of his summons to attend the King, Willis was a well-established provincial practitioner and madhouse proprietor. An anonymous French visitor published a description of Willis's Lincolnshire madhouse and his therapeutic practices in 1796. The translated text of the full article provides a unique insight into the work of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Long-term confinement had dire consequences, as reported in The Aberdeen Journal (Anon., 1846): ‘a maniac resides in a lonely little hovel, who has been chained to a pillar for many years’ with his body contracted. An anonymous French visitor to Francis Willis’s madhouse in Lincolnshire observed that confinement was ‘often fatal in its consequences’ (Smith and Peters, 2017: 373). (Willis became famous for treating George III’s madness.)…”
mentioning
confidence: 99%
“…Long-term confinement had dire consequences, as reported in The Aberdeen Journal (Anon., 1846): ‘a maniac resides in a lonely little hovel, who has been chained to a pillar for many years’ with his body contracted. An anonymous French visitor to Francis Willis’s madhouse in Lincolnshire observed that confinement was ‘often fatal in its consequences’ (Smith and Peters, 2017: 373). (Willis became famous for treating George III’s madness.)…”
mentioning
confidence: 99%